Automatic detection of break-over phase onset in horses using hoof-mounted inertial measurement unit sensors - Tijssen, M.; Hernlund, E.; Rhodin, M.; Bosch, S.; Voskamp, J. P.; Nielen, M.; Serra Braganca, F. M. (PLOS ONE, 2020)
Correction